Gespräche mit Künstlern. - Haase, Amine (Köln : Wienand Verlag)
Asmus, Dieter ; Baselitz, Georg ; Becher, Berhard und Hilla ; Beuys, Joseph ; Buthe, Michael ; Christian, Abraham David ; Darboven, Hanne ; Gerz, Jochen ; Götz, Karl Otto ; Graubner, Gotthard ; Gruber, Hetum ; Grützke, Johannes ; Hein, Wilhelm und Birgit ; Klapheck, Konrad ; Klauke, Jürgen ; Oppermann, Anna ; Petrick, Wolfgang ; Richter, Gerhard ; Rinke, Klaus ; Rosenbach, Ulrike ; Ruthenbeck, Reiner ; Schad, Christian ; Schult, HA ; Staeck, Klaus ; Uecker, Günther ; Vogt, Peter
boek